Macrocriminology and Freedom - Braithwaite, John (Peacebuilding Compared, 2022)
How can power over others be transformed to 'power with'? It is possible to transform many institutions to build societies with less predation and more freedom. These stretch from families and institutions of gender to the United Nations. Some societies, times and places have crime rates a hundred times higher than others. Some police forces kill at a hundred times the rate of others. Some criminal corporations kill thousands more than others. Micro variables fail to explain these patterns. Prevention principles for that challenge are macrocriminological. Freedom is conceived in a republican way as non-domination. Tempering domination prevents crime; crime prevention reduces domination. Many believe a high crime rate is a price of freedom. Not Braithwaite. His principles of crime control are to build freedom, temper power, lift people from poverty and reduce all forms of domination. Freedom requires a more just normative order. It requires cascading of peace by social movements for non-violence and non-domination. Periods of war, domination and anomie cascade with long lags to elevated crime, violence, inter-generational self-violence and ecocide. Cybercrime today poses risks of anomic nuclear wars. Braithwaite's proposals refine some of criminology's central theories and sharpen their relevance to all varieties of freedom. They can be reduced to one sentence. Strengthen freedom to prevent crime, prevent crime to strengthen freedom.